Značilnosti zaraščanja na opuščenih kmetijskih zemljiščih v Halozah - Cojzer, Mateja (Acta silvae et ligni, 2019)
The aim of the research was to study the characteristics and pathways of the successional development of shrubs and tree species on abandoned agricultural land in the Haloze region. Forests and abandoned lands have been increasing in this region for several decades. Thus, we studied the trends of this increase. We compared the species composition on abandoned land with that of forest in the young development phase. We also examined succession strategies on abandoned land. The forest area in the Haloze region increased by 7.8 % between 1985 and 2015. On abandoned agricultural land, succession begins with shrub species and continues with an increasing number of tree species along with an augmentation in tree density. The successional process proceeds through the Cornus sanguinea - Cornus sanguinea - Carpinus betulus stages. In the young development phases of the forest, tree species predominate from the beginning of succession, the density of individuals decreases during succession, and the number of species does not change significantly. The secondary succession pathway on abandoned land progresses through various stages from shrubs to climax vegetation. The final vegetation stage in both cases is beech forest.
Keywords: abandoned agricultural land; density of individuals; dominant species; dominantne vrste; gostota osebkov; Haloze; importance value; old-field succession; pomembnost vrste; Shannonov indeks pestrosti; Shannon's index; species composition; sukcesijski procesi zaraščanja; the Haloze region; vrstna sestava; zaraščajoča se kmetijska zemljišča